Assessment of Sleep Quality and Its Determinants Among Patients with Type 2 Diabetes Mellitus in Mogadishu, Somalia: A Cross-Sectional Study - Mohamed NA; Haji Mohamud RY; Hilowle FH; Ali TA; Mohamed YA; Gabow AA; Mohamed HN; Sidow NO; Hassan MS; Waberi MM (Diabetes, Metabolic Syndrome and Obesity)
Nur Adam Mohamed,1,2 Rahma Yusuf Haji Mohamud,3 Fadumo Hussein Hilowle,3 Tigad Abdisad Ali,4 Yusuf Abdirisak Mohamed,1,5 Adan Ali Gabow,1 Hawa Nuradin Mohamed,6 Nor Osman Sidow,7,8 Mohamed Sheikh Hassan,7 Mohamud Mire Waberi9 1Department of Psychiatry and Behavioral Sciences, Mogadishu Somali-Turkiye Recep Tayyip Erdogan Training and Research Hospital, Mogadishu, Somalia; 2Faculty of Medicine and Health Sciences, Jamhuriya University of Science and Technology, Mogadishu, Somalia; 3Department of Nursing, Mogadishu Somali-Turkiye Recep Tayyip Erdogan Training and Research Hospital, Mogadishu, Somalia; 4Department of Infection Prevention Control, Mogadishu Somali-Turkiye Recep Tayyip Erdogan Training and Research Hospital, Mogadishu, Somalia; 5Faculty of Medicine and Surgery, Somali National University, Mogadishu, Somalia; 6Department of Internal Medicine, Mogadishu Somali-Turkiye Recep Tayyip Erdogan Training and Research Hospital, Mogadishu, Somalia; 7Department of Neurology, Mogadishu Somali-Turkiye Recep Tayyip Erdogan Training and Research Hospital, Mogadishu, Somalia; 8Faculty of Medicine and Surgery, Jazeera University, Mogadishu, Somalia; 9Department of Cardiology, Mogadishu Somali-Turkiye Recep Tayyip Erdogan Training and Research Hospital, Mogadishu, SomaliaCorrespondence: Nur Adam Mohamed, Department of Psychiatry and Behavioral Sciences, Mogadishu Somali-Turkiye Recep Tayyip Erdogan Training and Research Hospital, Mogadishu, Somalia, Email nurmohed01@gmail.comBackground: Type 2 diabetes mellitus (T2DM) is a growing global health crisis, affecting hundreds of millions worldwide. Poor sleep quality—often under-recognized—impairs glycemic control and accelerates diabetes-related complications. Despite its clinical relevance, data on sleep quality among T2DM patients in Somalia are virtually nonexistent. This study aimed to evaluate the prevalence and determinants of poor sleep quality among T2DM patients in Mogadishu, Somalia.Methods: A hospital-based cross-sectional study was conducted between November 2024 and January 2025 at Mogadishu Somali-Turkiye Recep Tayyip Erdogan Training and Research Hospital. A total of 311 adults with T2DM were selected using systematic sampling. Data were collected using structured questionnaires and validated instruments including the Pittsburgh Sleep Quality Index (PSQI), Patient Health Questionnaire-9 (PHQ-9), and Oslo Social Support Scale (OSSS-3). Logistic regression analysis was employed to identify variables independently associated with suboptimal sleep quality.Results: Overall, 54.0% of participants reported poor sleep quality (95% CI: 48.3– 59.7). Multivariable analysis identified several significant predictors, including female gender, unemployment, low income, substance use, physical inactivity, and depressive symptoms. Clinical factors such as comorbidities, poor glycemic control, and diabetes-related complications were also independently associated with suboptimal sleep quality.Conclusion: Over half of T2DM patients in Mogadishu experience poor sleep quality, influenced by sociodemographic, behavioral, psychological, and clinical factors. The findings highlight the need to incorporate sleep evaluation and targeted interventions—focusing on mental health, lifestyle, and metabolic control—into routine diabetes care.Keywords: type 2 diabetes mellitus, sleep quality, determinants, Mogadishu, Somalia